Changes in perceived centrality of anxious events following cognitive behavioral therapy for social anxiety disorder and panic disorder. (June 2018) - O'Toole, Mia Skytte; Watson, Lynn; Rosenberg, Nicole K.; Berntsen, Dorthe
Abstract: Background and objective: The purpose of the present study was to explore the association between reductions in symptoms of psychopathology and perceived centrality of negative autobiographical memories in participants with social anxiety disorder (SAD) or panic disorder (PD). Methods: Thirty-nine individuals with SAD or PD recalled and rated four negative autobiographical memories before and after ten sessions of cognitive behavioral therapy (CBT) over a three-month period. Twenty-eight healthy controls did the same before and after a three-month period. Results: As hypothesized, results showed a decrease in perceived centrality following CBT. This decrease in perceived centrality was larger, although at the trend level, for individuals who experienced reliable change on disorder-specific symptoms. Limitations: The correlational nature of the study prevents establishing the causal relationship between changes in perceived centrality and psychopathology, and future studies should explore such mechanisms. Conclusions: The present study adds to the emerging body of literature, investigating changes in centrality of event following psychotherapy. Highlights: Individuals with SAD and PD recalled past negative events before and after CBT. A decrease in perceived centrality of event was detected following CBT. The decrease in perceived centrality was largest for individuals benefitting from CBT.